Young women’s opinion on the preferred family model - Misztal-Okońska, Patrycja; Wdowiak, Artur; Krawczyk, Wojciech; Młynarska, Magdalena (Polish Journal of Public Health, 2019)
Introduction. Currently in Poland second demographic transition takes place, main features of it being the drop of the birth rate, postponing the decision of starting a family and having children. Moreover, more people decide to live alone and do not have offspring. These processes lead to great change of the demographic structure of the country, for example low birth rate do not allow for the generational replacement. In addition, with extending the life expectancy, we observe society aging. In the future perspective we can expect prolonging drop of the birth rate, and as a consequence, drop in the number of fertile population and growth in the percentage of after fertile age. Aim. The aim of the paper was to collect opinions of young women on the preferred family model and eliciting reasons that in their opinion determine decision of resigning from having more children. Material and methods. The method used was diagnosing survey and the technique was authors’ questionnaire. The number of 538 women aged 19 to 42 were questioned. Results. The majority of the questioned women would prefer to have a family with two children (M-51.91) and three children (M-34.4). At the same time, the majority of the questioned mothers (62.13%) had one child, 31.49% – two children and only 5.10% – had three children. In the opinion of the questioned women, two main reasons for decision about having less children are the unemployment and low salaries. Large percentage of women (every second one) is afraid of the negative attitude of the employer towards maternity leaves. Conclusions. One of the reason of giving up or postponing decisions about motherhood and having small number of children by those who decide to be mothers in Poland may be concerns about professional and economic situation